Paisagem cinematográfica: o NUDOC e a produção cultural nas décadas de 1980-1990 - Bastos, Adeilma Carneiro (2009)
This dissertation is related to the history of the cinema from Paraíba, having as a specific object the Film Documentation Center of the Federal University of Paraíba (NUDOCUFPB), established in 1979, which is a major locus of reflection and film production in the 1980s. Thus, we aimed to discuss its foundation, placed in the context of "modernization", as a result of the development of expansion policies of the Federal University of Paraíba in that time, when it stimulated the growth of the place of research and production, connected to the perspective of reflection and interference in local reality. NUDOC boosted film production and became an important place of intellectual and technical preparation for several filmmakers that still remain in this activity. In addition, we intended, in our analysis, to specify the paths of this film production, observing also the critics made for the ideological and aesthetic options adopted. Besides, we examined some of the films produced by the Center, linking this production with the concept of historical culture, understanding that the film institutions participate of the structure of historical cultures, either confirming or rejecting hegemonic perspectives.